The internal logic of the cosmos as 'justice' and 'reconciliation': micro-level perceptions in post-conflict Guatemala - Viaene, Lieselotte (Critique of anthropology, 2010)
Recently there has been greater interest from academics and practitioners in the role of 'traditional' justice mechanisms in politics of peace, reconciliation and transitional justice efforts after a period of large-scale human rights violations. However, this call for 'culturally sensitive' approaches remains at a rhetorical level. This article attempts to fill the knowledge gap of empirical local studies and focuses on post-conflict processes in Guatemala. It explores the actual and potential role of particularities of Mayan Q'eqchi' culture in local social reconstruction processes after the internal armed conflict. Based on extensive ethnographic field research, the article explores how concepts of justice and reconciliation are locally and culturally understood. It uncovers the existence of multiple ways of understanding these concepts and further, the fact that they are perceived very differently from interpretations in international law and transitional justice studies. Impunity, as defined by international law, is not the end of accountability, nor truth recovery or reparation. Here, the internal logic of the cosmos through an invisible spiritual force, fosters social and spiritual repair at community level, contributing to the lack of demands of justice by Q'eqchi' survivors